Discovering Open Access Trends in Engineering: A Bibliometric Analysis of Open Access Publications at a Large Research University. Issue 1 (2nd January 2023) - McAllister, James; Torres, Jonathan
ABSTRACT: Open Access (OA) publications can be useful for developing collections in academic libraries during times of fiscal hardship. Bibliometric analysis is a tool that librarians can use to aid their collection decisions. This study gathered data on engineering OA publications from a research university to determine the number and OA models most used in Web of Science (WoS) and Ei Compendex, and then analyzed 5 Journal Impact Factor and CiteScore rankings. The data indicates growth in the volume of OA publishing, suggesting that engineering faculty and researchers are gradually accepting the notion of publishing using OA models.